Potential uses of auditory nerve stimulation to modulate immune responses in the inner ear and auditory brainstem - Seicol, Benjamin J.; Guo, Zixu; Garrity, Katy; Xie, Ruili (Frontiers in Integrative Neuroscience, 2023)
Bioelectronic medicine uses electrical stimulation of the nervous system to improve health outcomes throughout the body primarily by regulating immune responses. This concept, however, has yet to be applied systematically to the auditory system. There is growing interest in how cochlear damage and associated neuroinflammation may contribute to hearing loss. In conjunction with recent findings, we propose here a new perspective, which could be applied alongside advancing technologies, to use auditory nerve (AN) stimulation to modulate immune responses in hearing health disorders and following surgeries for auditory implants. In this article we will: 1) review the mechanisms of inflammation in the auditory system in relation to various forms of hearing loss, 2) explore nerve stimulation to reduce inflammation throughout the body and how similar neural-immune circuits likely exist in the auditory system 3) summarize current methods for stimulating the auditory system, particularly the AN, and 4) propose future directions to use bioelectronic medicine to ameliorate harmful immune responses in the inner ear and auditory brainstem to treat refractory conditions. We will illustrate how current knowledge from bioelectronic medicine can be applied to AN stimulation to resolve inflammation associated with implantation and disease. Further, we suggest the necessary steps to get discoveries in this emerging field from bench to bedside. Our vision is a future for AN stimulation that includes additional protocols as well as advances in devices to target and engage neural-immune circuitry for therapeutic benefits.